Grip Strength Measurement in Baseball Pitchers: A Clinical Examination to Indicate Stride Length Inefficiency - Ryan Crotin; Dan Ramsey (North American Sports Medicine Institute, 2021)
# Background Ulnar collateral ligament injuries are rampant in the sport of baseball where kinetic chain impacts, stemming from misappropriation of stride length or changes that occur in competition due to fatigue, have not been evaluated for dynamic elbow stability effects. # Hypothesis/Purpose To examine the relationship between clinical measures of grip strength and altered stride length in baseball pitchers. It is believed that shorter stride lengths would reduce grip strength in baseball pitchers. # Study Design Crossover Study Design # Methods A total of 19 uninjured pitchers (15 collegiate and 4 high school) (age 18.63 ± 1.67 years, height 1.84 ± 0.054 m, mass 82.14 ± 0.054 kg) threw two simulated 80-pitch games at ±25% of their desired stride length recorded by motion capture with two force plates and a radar gun to track each throw. A handheld grip dynamometer was used to record the mean change in grip strength after games from baseline measures. Pairwise comparisons at baseline and post-game denoted grip strength changes and dominant grip strength offsets for stride length conditions. # Results Subjects with shorter stride lengths revealed a significant decline in grip strength in the dominant arm from baseline (pre-game; 45.1 kg vs. post-game; 43.2 kg, p=0.017, ES=0.28), however all other tests involving dominant grip strength changes and offset analyses were not statistically different for under-stride and over-stride length conditions. # Conclusions Clinical evaluation of grip strength has the potential to identify altered lower body mechanics and may be considered as a safe and effective monitoring strategy to integrate with motion capture in determining optimal stride lengths for baseball pitchers. # Level of Evidence Level 3